Honeybees of Asia editors. - Hepburn, H. R.; Radloff, S. E. (Sarah E.) 1948- (Springer, 2011)
A multi-authored work on the basic biology of Asian honeybees, written by expert specialists in the field, this book highlights phylogeny, classification, mitochondrial and nuclear DNA, biogeography, genetics, physiology, pheromones, nesting, self-assembly processes, swarming, migration and absconding, reproduction, ecology, foraging and flight, dance languages, pollination, diseases/pests, colony defensiveness and natural enemies, honeybee mites, and interspecific interactions. Comprehensively covering the widely dispersed literature published in European as well as Asian-language journals and books, Honeybees of Asia provides an essential foundation for future research.